South Asia in the corona crisis: Economic and political consequences - Christian Wagner; Tobias Scholz (Stiftung Wissenschaft und Politik (SWP), 2020)
In the countries of South Asia, the rampant coronavirus pandemic could affect more than 1.9 billion people - almost a quarter of the world's population. Given the weaknesses of national health care systems, the fight against the virus seems to be lost before it has even begun. The economic damage will increase the levels of poverty and inequality, and it is likely to exacerbate rather than mitigate a number of existing conflicts. On the domestic front, it is feared that authoritarian tendencies will increase during the management of the crisis. In the regional context, China could further expand its influence at the expense of India.
Keywords: 320